A model for product innovation in the flavoured alcohol beverage industry in South Africa. - Moffat, Cleo Marcelle. (My University, 2014)
ABSTRACT Flavoured Alcohol Beverages (FAB’s) are perceived as trendy, desirable products and are particularly popular among image conscious consumers within the 18-26 year old age group. Packaged similarly to bottled beer and with drinking straight from the bottle, FAB makers have aligned their products in consumer minds with familiar beer products, which has boosted consumer acceptance of the product. Although brand imaging and recognition are important throughout the alcoholic drinks market, the FAB consumer population are extremely fickle and will consistently trade and experiment between brands, this fact drives this category to be extremely competitive and in need of constant innovation. This research models the best practice in new product development/innovation of flavoured alcohol beverages. The techniques employed, include open ended questions, the Delphi technique, using the opinions of industry experts, and modelling using Fuzzy Cognitive Mapping (FCM). The foremost findings of this report are that in order for innovation to be successful the key success factors of best practice innovation techniques must be addressed and these should be combined to ensure sustainability of an organisation’s innovation program. It was further discovered that due to the challenges of industry regulation, high rate of new competitor products and a challenging economic environment in South Africa, an organisation has to foster an entrepreneurial approach to ensure success in FAB innovation.
MBA 2014
Keywords: Alcoholic beverage industry, Alcoholic beverages, New products -- Management.